Analysing the effectiveness of visual aids for learning in Kuala Lumpur Bird Park - Sirajulfikri, Aina Syahirah; Mohd Lazim, Nur Aniza; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
This study explored the effectiveness of visual aids in enhancing learning experiences at the Bird Education Centre in Kuala Lumpur Bird Park, an informal educational setting aimed at promoting bird conservation awareness. The research focuses on visual learning tools such as egg incubator display, educational illustrated wall, data table, and documentary video, and how these tools influence visitor understanding, engagement, and retention. A quantitative research method was used, and data were collected through a structured survey questionnaire involving 55 visitors of varying demographic backgrounds. The results showed that visual materials such as data tables and illustrated walls were rated as the most engaging and helpful in supporting bird education. However, documentary videos were found to be the least preferred, which contrasts with previous research emphasizing the role of documentaries in wildlife education. The study also revealed that gender and age groups slightly influenced preferences and learning engagement, with female and younger visitors showing higher interaction levels with visual aids. Overall, the findings suggest that well-designed, accessible visual materials significantly improve visitor learning in nature-based environments. These insights may benefit educators, exhibit designers, and park planners in developing more effective and engaging educational tools for environmental awareness.